2020
DOI: 10.1111/apt.15769
|View full text |Cite
|
Sign up to set email alerts
|

Editorial: increasing IBD prevalence and its complications in the context of the COVID‐19 pandemic. Authors' reply

Abstract: Study of Inflammatory Bowel Disease (IOIBD) has undertaken a RAND panel of expert opinion regarding the care of IBD patients during the In time the evidence to support clinical recommendations is likely to develop. Others from epicentres of the COVID-19 pandemic have also given specific recommendations based on their experience. 10The paper by King et al reminds us of two important and interacting challenges facing IBD clinicians in the future. First, we will continue to see more IBD as the prevalence increas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 7 publications
(6 reference statements)
0
3
0
Order By: Relevance
“…Only 44 % of them have been to a clinic in the past three years. During the current coronavirus pandemic, an increased incidence of IBD has been documented [ 76 ]. As anxiety in IBD patients is more common because of social distancing and isolation in COVID-19 as described previously [ 77 ], it may worsen patients' condition, which might not be underestimated.…”
Section: Ibd In Covid-19 and Possible Probiotic Rolementioning
confidence: 99%
“…Only 44 % of them have been to a clinic in the past three years. During the current coronavirus pandemic, an increased incidence of IBD has been documented [ 76 ]. As anxiety in IBD patients is more common because of social distancing and isolation in COVID-19 as described previously [ 77 ], it may worsen patients' condition, which might not be underestimated.…”
Section: Ibd In Covid-19 and Possible Probiotic Rolementioning
confidence: 99%
“…It has been found that the incidence rate of IBD increased during the outbreak of COVID‐19. 41 SARS‐CoV‐2 can enter human cells through the recognition of ACE2 receptor, which is also highly expressed in the intestine. 42 , 43 Generally speaking, virus infection can damage the intestinal mucosa, destroy the digestion and absorption function of the intestine, affect the absorption of water by the intestine, and lead to enteritis.…”
Section: Association Between Covid‐19 and Ibdmentioning
confidence: 99%
“…It has been found that the incidence rate of IBD increased during the outbreak of COVID‐19 41 . SARS‐CoV‐2 can enter human cells through the recognition of ACE2 receptor, which is also highly expressed in the intestine 42,43 .…”
Section: Association Between Covid‐19 and Ibdmentioning
confidence: 99%